REBRANDING PRODUK KERIPIK JAMUR TIRAM UNTUK PENINGKATAN PENJUALAN PADA UMKM SPORAMUSHROOM - Mundiyah, Andi Iva; Septiadi, Dudi; Nabila, Sharfina; Sari, Ni Made Wirastika; Zeamita, Ni Made (Jurnal Pengabdian Kepada Masyarakat MEMBANGUN NEGERI, 2020)
ABSTRACT Small-Medium Enterprise (SME) ?Sporamushroom? which processes pearl-oyster mushrooms into pearl-oyster mushroom chips is located on Jalan Pelita, Makassar City. Pearl-oyster mushrooms are rich in nutrition and have savory taste and chicken-like texture, so that almost all people like it. The problem faced by SME ?Sporamushroom? lies in the packaging of the mushroom chips that are not attractive and are not able to preserve the quality of the products contained therein. In addition, the mushroom chips brand have not been determined. The results of the activities carried out indicate the need for assistance and information sharing about the types of packaging for processed chips, so that the packaging will be produced accordingly, which is aluminum plastic packaging that is suitable for processed chip products. From the brand aspect, the selection of the right and easy-to-remember brand has an effect on product sales. The JAMBUL brand was chosen as the brand of pearl-oyster mushroom chips because it is easy to be remembered and has appropriate philosophy behind it. Key words: brand, marketing, packaging, SME